PENGEMBANGAN PERANGKAT PEMBELAJARAN COOPERATIF LEARNING TIPE AUDITORY INTELECTUALLY REPETITION (AIR) UNTUK MENINGKATKAN PENGUASAAN KONSEP PADA MATERI USAHA DAN ENERGI - Yohani Dewita; Zuhdi Ma’aruf; Yennita Yennita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract : The purpose of this study was to develop learning materials for cooperative learning models of auditory intellectually repetition (AIR) learning model on work and energy for class X high school students. Device development was carried out as a solution to improve conceptual mastery in physics learning. The type of research used is research and development (R&D) using a 4D model, namely define, design, development, and disseminate. The data collection instrument was in the form of a validation sheet given to three validators. The data analysis technique was obtained by using a validation assessment score to determine the feasibility of the learning device. The results showed that the learning device of cooperative learning learning model type auditory intellectually repetition (AIR) on the work and energy for class X high school students that was developed met the valid criteria from the aspects that were validated including aspects of RPP feasibility, LKPD feasibility aspects and feasibility aspects of Concept Mastery Instruments.Key Word : learning devices, cooperative learning learning model type auditory intellectually repetition (AIR), Work and Energy